2015
DOI: 10.1080/16089677.2015.1030858
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic nephropathy in a tertiary care clinic in South Africa: a cross-sectional study

Abstract: Objective: The aim of this study was to determine the prevalence of micro-or macroalbuminuria in type 1 and type 2 diabetic patients, and to examine the relationship with the diabetes control parameters such as haemoglobin (Hb)A 1c , blood pressure (BP) and lipids. Design: This was an analytical cross-sectional study. Setting and subjects:The study consisted of 754 patients with either type 1 or type 2 diabetes, attending a diabetes clinic at the Kalafong Hospital in Pretoria, South Africa. Outcome measures: M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Four studies in South Africa and East Africa made use of mobile testing vans in rural areas. This method was particularly useful in reaching younger male populations, who are known to typically not access health facilities in this region [3538]. Three studies involved testing campaigns; one employed network based approaches to increase screening for at-risk individuals while another testing campaign was carried out by an independent humanitarian organisation to increase testing in vulnerable populations.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies in South Africa and East Africa made use of mobile testing vans in rural areas. This method was particularly useful in reaching younger male populations, who are known to typically not access health facilities in this region [3538]. Three studies involved testing campaigns; one employed network based approaches to increase screening for at-risk individuals while another testing campaign was carried out by an independent humanitarian organisation to increase testing in vulnerable populations.…”
Section: Resultsmentioning
confidence: 99%
“…Ngassa Piotie et al demonstrated a similar outcome in their 2015 Pretoria-based study where 88.9% of their patients had HbA1c values exceeding 7%. 9 …”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 Using albuminuria as a marker of diabetic nephropathy, Ngassa Piotie et al demonstrated a prevalence of 33.6%. 9 A Cape Town-based study showed a prevalence of stage 3–5 CKD in 23.9% of 1202 participants of mixed ancestry. Concomitant DM was identified in 26.4% of this cohort.…”
Section: Introductionmentioning
confidence: 99%
“…At best, only approximately 1 out of every 4 patients with type 2 diabetes achieves HbA1c < 7%. [23][24][25][26][27][28][29][30][31][32][33][34] However, currently, there are few or no data on usual prescribing practices for patients with diabetes in South Africa.…”
Section: Introductionmentioning
confidence: 99%